Perinatal mental health care from the user and provider perspective: protocol for a qualitative study in Switzerland - Anke Berger; Karin Schenk; Ankica Ging; Sebastian Walther; Eva Cignacco (BMC, 2020)
Abstract Background Mental disorders in the perinatal period (PMD) can severely harm women and their children if not detected early and treated appropriately. Even though mental health care is covered by health insurance and is used widely by women in the perinatal period in Switzerland, it is not known if the care provided is meeting the needs of the patients and is efficient in the view of health care professionals. The aim of this study is to identify strengths, gaps and requirements for adequate mental health care in the perinatal period from the perspectives of patients and care providers for a wide range of relevant mental disorders. Methods In the qualitative study we conduct (1) semi-structured single interviews with former PMD patients to obtain narratives about their experiences and needs for health care for their condition. Women are included who have been treated for PMD but are mentally stable at the time of the interview (n = 24). We will stratify the sample by 4 clusters of relevant ICD-10 F-diagnoses, covering the most frequent and the most severe mental disorders. We will further stratify the sample based on whether the women already had experience with psychiatric or psychological health care or not before their last episode of PMD. We will also conduct (2) three interprofessional focus groups with health and social care professionals involved in perinatal care, and a health insurance representative. The focus groups will consist of 5-8 professionals. Data collection and thematic analysis will consider Levesque's et al. (2013) conceptual model on access to health care. Discussion The study will provide fundamental data on the experiences and perspectives about perinatal mental health care from user and provider perspectives. The study will generate the evidence base needed to develop models of integrated, coordinated, patient- and family-centred care that is accessed by women with various types of PMD. Trial registration The study was registered on ClinicalTrials.gov in November 2019 under the identifier NCT04185896.